(untitled) (Ameghiniana, 2013)
The principal diagnostic characters of Cladophlebis mainly as pointed out by Frenguelli (1947) on Brongniart’s original, are accepted with only a few additions and restrictions. After that, a sistematic description of all the species accepted validly for Argentina is given, with indications of: paper of original diagnosis, original locality and age, type-specimens, other cites from Argentina and arguments for their acceptance. A list of these species is found in page 267. A further chapter is devoted to discuss those species whose presence is not accepted because of: wrong determinations, too fragmentary material, etc. Finally, table 1 shows the geographic and geologic distribution of all the species represented in Argentina. Tentatively, they are-grouped into: I) Triassic, II) Trias-jurassic, III) Liassic, IV) Jura-Lower Cretaceous and V) Cretaceous species. These groups don’t have any but empirical value.